INSTAGRAM REELS CONTENT ANALYSIS ON CULINARY PREFERENCES ON BENGKULU CULINARY INSTAGRAM ACCOUNTS - Nelis Juniarti; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
Research is to determine the influence of Bengkulu culinary Instagram accounts on people's culinary preferences. Instagram can be the most strategic social media for marketing, because it can influence a person's behavior or interests. This is because content differentiates an account compared to other accounts. Consumer purchasing behavior is initiated and influenced by many stimuli from outside themselves. These stimuli can be marketing stimuli or stimuli from the surrounding environment. Therefore, it is necessary to know what factors can influence people's culinary preferences from Instagram culinary accounts. The results of this research are: Based on the results of observations made by researchers, it is known that the admin of the @kulinerbengkulu Instagram account also utilizes the reels feature, which is currently viral, used by the entire public and including well-known Indonesian artists. The information provided in the Reels feature on Instagram @kulinerbengkulu contains culinary information in Bengkulu.